Exploring the aspirations of Kolkatan (Calcuttan) Street Children using drawings - MERRIMAN, BRIAN (Universidad de Almeria / Asociacion de Analisis del Comportamiento, 2007)
The aims of the present study were to represent the aspirations of Kolkatan street children and to draw comparisons across gender and between children "on the streets" and "off the streets". The participants were 151 Street Children from Kolkata (Calcutta), India, 66 males (43.7%) and 85 females (56.3%), of which 51 (33.8%) were "on the streets" and 100 (66.2%) were "off the streets". They were asked to draw a picture of the sort of person they wanted to be when they grew up and to write who the person was, what they were doing, and why they were chosen. Content analysis identified themes evident in the drawings and comments. Frequency analysis and chi-square tests were used to identify patterns in these themes. Kappa coefficients for inter-rater reliability on a random sample of 10% of drawings reached the minimum 0.7 level for all themes. The most common occupations recorded were Teacher (n= 48, 31.8%), and Doctor, (n= 29, 19.2%) and there was a majority of higher socio-economic status (SES) occupations with high Educational requirements. Boys were more likely to draw male stereotypes and girls non-gender specific roles. Girls were more likely than boys to depict Helping as a Contribution and boys more likely than girls to depict Defence. These results are discussed with reference to patterns of themes identified and to the role of gender in some of the differences. Finally, some of the difficulties with the present study are posed as potential questions for further research.
PUBLISHED
Keywords: Psychology; Drawings; Career aspirations; Street Children